2008
DOI: 10.1177/135965350901400307
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of lipodystrophy and metabolic disorders in patients starting non-nucleoside reverse transcriptase inhibitors in Benin

Abstract: Background The incidence and risk factors for lipodystrophy and metabolic disorders among patients in Africa on first-line combined antiretroviral treatment (cART) mostly containing non-nucleoside reverse transcriptase inhibitors is poorly documented. Methods This prospective cohort study recruited 88 HIV-infected patients initiating cART between October 2004 and June 2005 in Cotonou, Benin. Patients were followed for 24 months. The main outcomes were incidence of lipodystrophy and metabolic disorders. Multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(9 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…This study is consistent with research ndings in Cameron (11.3%) [28], Iran (11.6%) [29], Senegal (14.5) [30], and Saud Araia (15.4%) [31]. However, it is higher than the prevalence reported in Eastern Ethiopia, Harar (7.1%) [12], and Benin (7.6%) [32]. The difference in the prevalence of diabetes between different studies could be attributed to differences in the population demographics, genetic factors, lifestyle factors, and healthcare access and infrastructure across the regions studied.…”
Section: Discussionsupporting
confidence: 91%
“…This study is consistent with research ndings in Cameron (11.3%) [28], Iran (11.6%) [29], Senegal (14.5) [30], and Saud Araia (15.4%) [31]. However, it is higher than the prevalence reported in Eastern Ethiopia, Harar (7.1%) [12], and Benin (7.6%) [32]. The difference in the prevalence of diabetes between different studies could be attributed to differences in the population demographics, genetic factors, lifestyle factors, and healthcare access and infrastructure across the regions studied.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies [20–22] have also implicated Pis in the development of MetS. However, some studies have shown contrary results [23–25]. In our study, there were no differences in the prevalence of MetS among people living with HIV with different ART regimens in the univariate analysis.…”
Section: Discussioncontrasting
confidence: 77%
“…Comparable increases in obesity prevalence among non-HIV-infected individuals are associated with increased chronic disease morbidity and mortality. Coupled with HIV infection (for example, inflammation and immune activation) and ART medication contributions to non-AIDS morbidity, this high prevalence of obesity places HIV-positive patients at great risk [9,[25][26][27][28]. The confluence of obesity and HIV infection probably exacerbates risk for comorbidities such as diabetes, cardiovascular disease and other conditions, highlighting the need to aggressively manage obesity and its related comorbidities in the ageing HIV-infected populace.…”
Section: Discussionmentioning
confidence: 99%